Taguchi optimisation approach for chromium removal in a rotating packed bed contractor - Kundu, A.; SenGupta, B.; Hashim, M.A.; Redzwan, G. (Elsevier, 2015)
Rotating packed bed (RPB) is a doughnut shaped bed, which is spun at high speed to generate centrifugal force to pass fluid through an adsorbent bed at a high velocity. The centrifugal force, which is much larger than the gravitational force reduces mass transfer resistance for transporting adsorbate molecules to the adsorbent. In this study, the optimum condition of the working parameters of a RPB contactor for removal of chromium by activated carbon was investigated with the aid of Taguchi method. Four parameters, namely, rotating speed (rpm), feed rate (L/h), packing density (kg/m(3)) and initial solution pH were chosen as the control factors while initial concentration of chromium was chosen as the external noise factor. The optimum condition for the adsorption was found to be rotating speed (rpm) of 1200 (level 3), feed rate (L/h) of 50 (level 4), packing density (kg/m(3)) of 179 (level 3), and initial solution pH of 2 (level 1). The experimental and predicted S/N ratios with values 39.26 and 39.20 were in very good agreement with each other at the optimum condition. A removal of 91% was obtained at the optimum condition. Pseudo second order kinetics described the adsorption rate satisfactorily while the mechanism could be described by the film diffusion model. (C) 2015 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.